(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
This research aims to determine the factors that influence the use of accounting information in UMKM in Timika City. The data collected in this research is quantitative and qualitative data using questionnaire techniques. Data analysis in this study used SEM PLS analysis. From the results of the analysis that has been carried out, the research results show that habit variables, usefulness variables and business scale variables have a significant effect on the use of accounting information in UMKM. Meanwhile, the knowledge variable does not have a significant effect on the use of accounting information in UMKM in Timika City. Keywords: UMKM, Knowledge, Benefits, Business Scale, Habits and Use of Accounting Information